Uniaxial compression of suspended single and multilayer graphenes. (10th June 2016) - Sgouros, A P; Kalosakas, G; Galiotis, C; Papagelis, K
Abstract: The mechanical response of single and multiple graphene sheets under uniaxial compressive loads was studied with molecular dynamics (MD) simulations, using different semi-empirical force fields at different boundary conditions or constrains. Compressive stress–strain curves were obtained and the critical stress/strain values were derived. The MD results are compared to the linear elasticity continuum theory for loaded slabs. Concerning the length dependence of critical values, qualitatively similar behavior is observed between the theory and numerical simulations for single layer graphenes, as the critical stress/strain for buckling was found to scale to the inverse squared length. However discrepancies were noted for multilayer graphenes, where the critical buckling stress also decreased with increasing length, though at a slower rate than expected from elastic buckling analysis.